IMPROVING INTEGRATED THEMATIC LEARNING PROCESS USING THE PROBLEM BASED LEARNING MODEL - Ariyati, Rohayana; M.Pd, Dra. Rahmatina; M.Pd, Dra. Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the teacher's inability to implement integrated thematic learning, especially in stimulating students to think critically in solving problems. This study aims to describe how to improve integrated thematic learning with Problem Based Learning models in class IV SDN 08 Campago Ipuh. This research is a classroom action research (CAR). Conducted in two cycles, with 3 meetings. The research flow includes planning, implementing, observing, and reflecting. The instruments used are observation sheets and test sheets. Research subjects were teachers and fourth grade students of SDN 08 Campago Ipuh Bukittinggi, totaling 26 students. The results showed an increase in: a) RPP in the first cycle on average 77.5% (B), cycle II 94.4% (SB), b) Implementation in the aspect of teachers in the first cycle on average 69.8% (B ), cycle II 92.8% (SB), while in the aspect of students in the first cycle on average 75% (B), cycle II 92.8% (SB). Thus, it can be concluded that the PBL model can improve the integrated thematic learning process in primary schools.